Toward Islamic Political Economy at the Turn of the Century - Masudul Alam Choudhury (International Institute of Islamic Thought, 1996)
Background and Some Explanatory Terms With the distancing of Muslim societies from the pristine tawhidi (unity of God) origins of the Qur’an ingrained in the Madinah Charter (metareligious constitution of the earliest organized Islamic state)’ as the experience of the Prophet Muhammad during his flight to the realm of knowledge across the sidrat al rnuntaha (the tree/region of perfect knowledge, i.e., bliss), their constitutional strengths of life and thought decayed exponentially. This marked both the intolerance and the increasing severance of the Muslim community from the roots of Qur’anic epistemology. Neither rationalism, scholasticism, nor controlled clerical dominance (fatwas) can be the methodology to replace the otherwise unifying epistemology of tawhidi precept in all walks of life. Unification epistemology (also termed alternatively as tawhidi epistemology and unity precept equivalent to Qur’anic epistemology) is the worldview that establishes life, thought, and their cognitive constituents in the fold of a universally interactiveintegrative pervasion of inter- and intrasystemic relationships. In this fold, God-Man-Universe interrelationships are framed according to precise principles. These principles then ground the emergence of laws that remain integral with the unifying epistemology. The emergence and convergence of all processes in this framework are then seen to uphold cause-effect relationships with a uniquely irreducible and logical presence of unity. The worldview of unification epistemology is premised in this methodical deconstruction of all processes to the irreducible core that foundationally unifies all relationships and that is, in turn, reflected in the self-referential conclusions of all unified systems. What else can that irreducible, unified epistemological premise be but tawhid! While the ...